SISTEM INFORMASI AKUNTANSI DALAM PENGELOLAAN PENGHIMPUNAN DANA NASABAH - Haryanti, Nik (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2016)
The role of accounting information systems, especially in terms of provision of credit necessary to support the provision of transactions that are reliable and accurate, minimize data redundancy, to provide data storage capacity is good and easily accessible, supporting decision-making, especially in analyzing creditworthiness, as well as supporting the processing of data into information that is useful to management in the form of journals, reports, and dokumen.Produk fund that uses the same legal implications prinsipwadi'ah with qardh, in which the customer acts as a bank that lends money and acting as lender.